Analisis Persediaan Bahan Baku dan Pemilihan Supplier Berbasis Continuous Review System dan Analytical Hierarchy Process - Lastriana Reza Nurlintang; Siti Muhimatul Khoiroh (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
PT. XYZ is a footwear manufacturing company that implements a make-to-order production system, requiring effective raw material inventory control and appropriate supplier selection to support smooth production activities. This study aims to analyze raw material inventory control using the Continuous Review System (s,S) method and determine priority suppliers using the Analytical Hierarchy Process (AHP) method. The research data were collected through observations, interviews, company documentation, and questionnaires distributed to parties involved in raw material procurement. The results showed that the reorder point and maximum inventory values for Canvas were 85,351 m and 88,616 m, Mesh Fabric were 44,217 m and 46,424 m, and Lining Fabric were 18,477 m and 20,317 m, respectively. The AHP results indicated a Consistency Ratio value of 0.0925, meaning the assessment was consistent. Supplier 1 obtained the highest weight value of 0.5057 (51%), making it the company’s priority supplier.